Internal Medicine Residents and the Practice of Defensive Medicine: A Pilot Study Across Three Internal Medicine Residency Programs - Borgan, Saif M (Cureus, 2020)
Background Defensive medicine is becoming increasingly prevalent in the United States and is estimated to cost billions of dollars in excess healthcare spending. There is evidence that the practice of defensive medicine starts early in the medical career. Defensive medicine has been investigated among residents in high medico-legal risk specialties, but there is a paucity of information on its prevalence among internal medicine residents. Objective  To examine the prevalence and patterns of defensive medical practices among internal medicine residents. Methods We conducted an online survey among the residents of three internal medicine residency programs in the 2018-2019 academic cycle. We invited all internal medicine residents within the selected programs to participate through email and asked them to complete an electronic survey assessing defensive medical practices. Results A total of 49 out of 143 residents participated in the study (response rate: 34.3%); 55% (n = 27) of the residents who participated considered the risk of being sued during residency to be low, compared to 40.8% (n = 20) who considered it to be moderate and 4.1% (n = 2) who considered it to be high. Defensive medical practices were found to be widely prevalent (40.0-91.3%) among internal medicine residents across all three clinical training stages. Assurance defensive practices were more common than avoidance practices. Conclusion Defensive medical practices, especially of the assurance type, were widely prevalent among our sample of internal medicine residents.